Management and outcome of adult generalized tetanus in a Chinese tertiary hospital - An, Yuling; Guo, Yi; Li, Lijuan; Li, Ziyu; Fan, Mingming; Peng, You; Yi, Xiaomeng; Lv, Haijin (Frontiers in Public Health, 2024)
Background Tetanus is a rare surgical infectious disease with a high reported relevant mortality. It still remains a serious problem in public health, particularly in low-income and middle-income countries. The purpose of this study was to investigate the management and prognosis of adult generalized tetanus in our hospital. Methods A total of 20 adult generalized tetanus patients were recruited in this retrospective observational study. Patients were retrieved from the hospital data base via discharge diagnosis. Patients were divided into two groups (Severe or Non-severe tetanus group) based on the severity of tetanus by using the Ablett classification. The differences between the two groups were compared. Results The study included 11 males (55%) and 9 females (45%). All tetanus patients recovered. The median age was 53.5 years [IQR: 19–78]. There were 1 mild (Grade 1) case (5%),5 moderate (Grade 2) cases (25%), 2 severe (Grade 3) cases (10%), and 12 very severe (Grade 4) cases (60%). Nineteen patients (95%) did not have tetanus immunization before. The majority of patients were farmers (60%), and came from rural areas (60%). Thirteen (65%) patients had a history of puncture injury. The rate of wound debridement after admission was 60% overall. Thirteen (65%) patients required mechanical ventilation for a median of 21 [IQR:12–41] days. Autonomic instability occurred in 13 (65%) patients. Pulmonary infections occurred in 12 (60%) patients. Median duration of hospital stay was 29.5 [IQR:12–68] days. More patients in the Severe group needed ICU admission, wound debridement, mechanical ventilation and heavy sedation combined with muscle relaxants (p < 0.05). The hospital stay was significantly longer in patients in the Severe group (p < 0.05). Conclusion After effective treatment, all adult patients with generalized tetanus in this study were cured and discharged. Severe tetanus requires early ICU treatment, wound debridement and effective treatment of autonomic instability.